Isolation of nitrate reducetase gene in sago palm via polymerase chain reaction using gene - specific primers - Fatimah, binti Elie. (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The reduction of nitrate to nitrite catalyzed by nitrate reductase (NR) enzyme is considered to be the rate-limiting and regulated step of nitrate assimilation, a major metabolic pathway occurri ng in a wide range of organisms which in turn supply the nutritional nitrogen requirements for other forms of life. An attempt to identify and clone the gene which encodes for nitrate reductase enzyme in sago palm was carried out in this study. The mini-prep extraction of total genomic DNA from sago using eTAB method produced a satisfactory result whereby fine bands were observed on 1 % agarose gel electrophoresis. Isolated DNA was subjected to peR amplification using 2 sets of general NR primers. Due to the non-specificity of the primers used, the first trial of peR amplification produced multiple bands. However this has been overcome by increasing the annealing temperature of the reaction. The fragments were excised from gel, then cloned into pGEM-T vector and subsequently transformed into E. coli JMI09. Selected white colonies obtained from the Luria Broth Agar plates were analysed to detect the presence of inserted DNA fragments. However restriction enzyme digestion of the plasmid failed to detect the presence of inserted fragment.